APCCS LEISURE AREAS AND COMPETITION TRAINING (Fiep Bulletin - online, 2025)
The production of implements, objects and tools by man in the search for improving living conditions and facilitating daily activities, made man an inventor of tools to help him in his daily life. In this context, the invention of the bicycle became relevant for urban mobility. It became a leisure instrument and later a sporting aspect in contemporary times, bringing to light numerous traffic accidents, which led to the creation of specific areas for the practice of cycling called APCC – Areas of Protection for Competitive Cycling. Objective: The study aimed to present the legal provisions that consecrated the creation of these areas in the city of Rio de Janeiro, together with the presentation of the chosen locations and their peculiarities. Methods: Documentary study, focusing on the analysis of the publications that make up the Organic Law of the Municipality of Rio de Janeiro and the Official Gazette of the City - RJ, together with the analysis of the website of the Municipal Department of Sports and Leisure – SMEL. Results/Conclusion: The results indicated the creation of the APCCs on May 17, 2013, through Bill 248/2013, which designated five areas for this purpose: Parque Radical Deodoro, Parque Madureira, Praia da Reserva, Aterro do Flamengo, Porto Maravilha, with the intention of being controlled spaces for the training of competitive cycling athletes, enabling the development of the sport in the city of Rio de Janeiro, which enjoys the attention of the State for the creation of legislation that meets the desires of this public.
Keywords: Cycling; Competition: Leisure; Traffic Safety